(untitled) (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: The objective of this study is to determine the effect of eel meat (Monopterus albus) extract ointment on an incision. Materials and Methods: The experimental animals used in this study were 20 male rats (Rattus norvegicus), Wistar, weighing 150–200 gm and aged 8–12 weeks. This study uses complete random design and is divided into four groups. In the negative control group, group treatment was carried out on the healthy rat. In the positive control group, the incision was performed without any therapy. In the T1 and T2 groups, group treatment was performed with a dose of 2% and 5% eel (M. albus) extracts. The TNF-α expression was analyzed by the immunohistochemistry (IHC) technique and epidermal thickness by Masson’s Trichrome (MT) staining. Data analysis of TNF-α expression and epidermal thickness was done using one-way analysis of variance and the Tukey test with a confidence level of 95% (α = 0.05). Results: The results showed that the eel (M. albus) extract therapy, with a concentration of 2% and 5%, significantly (p < 0.05) reduced the TNF-α expression and increased the epidermal thickness. Conclusion: It can be concluded that the administration of eel (M. albus) extract therapy could help to reduce TNF-α expression and increase epidermal thickness in rat incision wounds. J. Adv. Vet. Anim. Res., 7(1): 77-82, March 2020